Pelatihan Aritmatika dalam Menunjang Prestasi Siswa Siswi di Sekolah Dasar Negeri Purwakarta Cilegon - Deni Sunaryo; Aisya Nur Aini; Fadly Syuhada Daulay; Ridho Fadilah; Dede Torry Miharja; Abdul Fatah; Ahmad Firdaus (Lembaga Pengembangan Kinerja Dosen, 2024)
The intelligence of an elementary school teacher in delivering material needs to be supported by the family environment and the role of the student's parents. From here we know that improving and developing the quality of knowledge about Mathematics is important. Purwakarta State Elementary School students in Cilegon City find it easier to remember and understand Mathematics lessons if they enjoy doing it and are accompanied by real experiences in everyday life. The role of higher education through the Tridharma of Higher Education is to carry out education, research and community service. One form of this obligation and concern is that as a Permanent Lecturer or academic at Serang Raya University, I intend to carry out community service to the students of Purwakarta State Elementary School, Cilegon City through Arithmetic training. This community service aims to provide learning services that are tailored to the learning difficulties of students at the Purwakarta State Primary School, Cilegon City. This Community Service Activity (PKM) is carried out in the classrooms of each class. As a result of the tutoring activities carried out by tutors for students, it can be concluded that there has been an increase in student learning outcomes